Rectify [videorecording (DVD)] - Kirby, Luke, 1978-; Spencer, Abigail, 1981-; Young, Aden; Smith-Cameron, J. (Anchor Bay Entertainment, 2013)
After spending 19 years on Death Row for the rape and murder of his teenage girlfriend, Daniel Holden is going home. His conviction has been vacated due to new DNA evidence, thrusting him back into a world he no longer knows. As he struggles to adapt to his new life, his return will reignite the fears of a small town and threaten to shatter his family's fragile peace. Daniel's alleged crime divided a community. His freedom could tear it in half.